EFFECT OF PRE-OPERATIVE SERUM VITAMIN-D LEVELS ON POST-OPERATIVE OUTCOME IN TOTAL KNEE ARTHROPLASTY - Khan, Junaid; Ahmed, Riaz; Akhtar, Rahman Rasool (Journal of Postgraduate Medical Institute, 2019)
Objective: To determine the effect of pre-operative serum vitamin-D levels on the post-operative outcome in patients undergoing total knee arthroplasty. Methodology: This prospective cohort study was conducted at the Department of Orthopaedics, Benazir Bhutto Hospital, Rawalpindi, Pakistan from 11th May 2017 to 10th May 2018. A total of 110 patients undergoing primary unilateral total knee arthroplasty (TKA) were enrolled in the study. Patients were placed into two groups. Group A included patients who had deficient vitamin-D3 levels (<30 ng/ml) while group B had patients with sufficient levels of vitamin-D3 (â‰¥30 ng/ml). Functional evaluation was done pre-operatively and at 03 months post-operatively using American knee society score (KSS), Alternate step test (AST) and Six-meter walk test (SWT). Mean functional scores were compared using student's t-test in SPSS version 23. Results: There were 48 (43.64%) male and 62 (56.36%) female patients. Mean age of patients in group A was 60.87 ±5.10 years while in group B it was 60.09 ±4.78 years. Group A patients had mean vitamin-D levels of 13.56 ±6.12 ng/ml and those in group B had 41.49 ±9.95 ng/ml. At 3 months post-op, functional KSS showed a significant difference between the two groups (65.98 ±5.10 in group A and 74.87 ±5.02 in group B, p <0.01). The performance tests showed significant difference between the 02 groups (16.46 ±2.78 vs. 15.12 ±3.37, p =0.02 for AST) while (8.48 ±2.06 vs. 7.49 ±1.88, p =0.01, for SWT), respectively. Conclusion: Pre-operative vitamin-D levels significantly affect the post-operative functional outcome in TKA.